Screening for diabetes and prediabetes: the newest communication opportunities - V.I. Velychko; V.L. Mykhailenko; D.O. Lahoda; G.O. Volokhova; S.L. Liashenko (Publishing House TRILIST, 2021)
Type 2 diabetes mellitus (DM-2) and prediabetes are serious diseases that can lead to early disability and death. DM-2 can remain undiagnosed for many years; therefore, screening is one of the main assistants of a doctor in establishing a diagnosis, allowing to start treatment as early as possible. Research objective: early identification of patients with prediabetes and DM-2 using an online questionnaire. Materials and methods. The study was carried out online using the Google Forms platform, where a questionnaire was created based on Appendix 3 "Form of risk assessment of diabetes mellitus-2" of the Unified clinical protocol of primary and secondary (specialized) medical care "Type 2 diabetes mellitus", approved by order of the Ministry of Health of Ukraine No. 1118 dated 12.21.2012, as well as additional questions on nutrition and physical activity. As of June 2021, the study involved 209 patients (151 women and 58 men) who did not have a documented diagnosis of DM-2 or prediabetes. Results. Most of the respondents (89 people) were overweight. 51 respondents had grade I obesity, 31 respondents had grade II, and 7 patients had a body mass index > 40 kg/m2, which corresponds to grade III obesity. Only 49 respondents had a healthy weight, which corresponds to a body mass index 18.5-24.9 kg/m2. 29 (19.21%) women had a history of childbirth with a child weighing more than 4 kg. The diagnosis of polycystic ovary disease (a risk factor for the DM-2) was in 34 (22.52%) women. Upon receipt of laboratory tests, we established a diagnosis of prediabetes in 28 (13.40%) patients, and a diagnosis of DM-2 in 17 (8.13%) people. Conclusions. It is necessary to search for new opportunities in communicating with patients during the COVID-19 pandemic, one of which is online questionnaires based on regulatory documents.